1987
DOI: 10.1073/pnas.84.21.7443
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation mechanism of the cytotoxic and nephrotoxic S-conjugate S-(2-chloro-1,1,2-trifluoroethyl)-L-cysteine.

Abstract: The bioactivation of S-(2-chloro-1,1,2-trifluoroethyl)-L-cysteine (CTFC) was studied with purified bovine kidney cysteine conjugate beta-lyase and with N-dodecylpyridoxal bromide in cetyltrimethylammonium bromide micelles as a pyridoxal model system. The beta-lyase and the pyridoxal model system converted CTFC to chlorofluoroacetic acid and inorganic fluoride, which were identified by 19F NMR spectrometry. 2-Chloro-1,1,2-trifluoroethanethiol and chlorofluorothionoacetyl fluoride were formed as metabolites of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…This coincide with the pharmacokinetic disposition of TCE which have already been reported that exposed TCE is absorbed in intestinal tract, partially changed into glutathione conjugate in liver and transformed into DCVC in bile duct or intestinal tract. Subsequently, DCVC is reabsorbed in intestinal tract and transformed into active thiol by cysteine conjugate β-lyase in liver and kidney, and then the generated active thiol expresses toxicity in kidney (Dekant et al, 1987. The active thiol is chemically unstable, with higher reactivity than other thiols, which means thiols generated in other organs can hardly act in kidney via systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…This coincide with the pharmacokinetic disposition of TCE which have already been reported that exposed TCE is absorbed in intestinal tract, partially changed into glutathione conjugate in liver and transformed into DCVC in bile duct or intestinal tract. Subsequently, DCVC is reabsorbed in intestinal tract and transformed into active thiol by cysteine conjugate β-lyase in liver and kidney, and then the generated active thiol expresses toxicity in kidney (Dekant et al, 1987. The active thiol is chemically unstable, with higher reactivity than other thiols, which means thiols generated in other organs can hardly act in kidney via systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…respectively, as effective as 20 mML-phenylalanine in transaminase reactions catalyzed by purified rat kidney glutamine transaminase K. [Conditions were 100 mM ammediol HCI buffer (pH 9.0) containing 5 m M a-keto-y-methiolbutyrate at 37"C.I In the reverse direction, the corresponding naphthylpyruvates are -5-10% as effective as phenylpyruvate as substrates for glutamine transaminase K. [Conditions were 100 mil4 ammediol HCI buffer (pH 9.0), 0.4 mM a-keto acid, and 20 mML-glutamine at 37"C.I These findings are further evidence for the "open" nature o f the active site of glutamine transaminase K. fractions of rat kidney, and the kidney mitochondria are especially sensitive to cysteine conjugate-induced damage (see, e.g., Lash et al, 1986;Stevens et al, 1988). For several halogenated cysteine conjugates it has been shown that the reactive fragments released in the @-elimination reaction (a retro-Michael elimination) by the action of glutamine transaminase K/cysteine-S-conjugate P-lyase are strong thioacetylating agents (Dekant et al, 1987(Dekant et al, , 1988a. Direct binding of these fragments to macromolecules in isolated intact kidney mitochondria has been demonstrated (Hayden and Stevens, 1989;Hayden et al, 1991).…”
mentioning
confidence: 99%
“…The multiple enzyme systems of GST detoxify electro philes, formed as intermediate products of xenobiotic degradation, by conjugation with glutathione. However, these enzymes also serve as bioactivation mechanism pro ducing either cytotoxic or carcinogenic metabolites that may be involved in cell damage and death [17], The shift of the peak in GST activity from the 28th to the 7th day in groups 9 and 10 indicates glutathione-conjugation-dependent toxicity as exhibited by the shorter lifespan of the host. Similar observations of enhanced GST activity have been reported earlier in human lungs, breast and colon cancers [18][19][20], This increase in GST activity may be related to either tumour invasiveness or alteration in the hepatic environment as the GST enzyme family is neces sary for rapidly proliferating cells [20].…”
Section: Discussionmentioning
confidence: 99%